2016
DOI: 10.3390/ijms17101610
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Dexamethasone and Postnatal High-Fat Diet Decrease Interferon Gamma Production through an Age-Dependent Histone Modification in Male Sprague-Dawley Rats

Abstract: Overexposure to prenatal glucocorticoid (GC) disturbs hypothalamic-pituitary-adrenocortical axis-associated neuroendocrine metabolism and susceptibility to metabolic syndrome. A high-fat (HF) diet is a major environmental factor that can cause metabolic syndrome. We aimed to investigate whether prenatal GC plus a postnatal HF diet could alter immune programming in rat offspring. Pregnant Sprague-Dawley rats were given intraperitoneal injections of dexamethasone or saline at 14–21 days of gestation. Male offspr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…This intergenerational transmission of the GC effects is mainly mediated by epigenetic mechanisms [2, 4, 5]. In animals, the effects of prenatal GC treatment on the development of the immune system have been evaluated in small series, which indicated that prenatal GC treatment may result in the alteration of inflammatory factors [6, 7], and thus contribute to the disturbance of immune system. However, reports about the mechanism linked prenatal GC exposure and autoimmunity are few.…”
Section: Introductionmentioning
confidence: 99%
“…This intergenerational transmission of the GC effects is mainly mediated by epigenetic mechanisms [2, 4, 5]. In animals, the effects of prenatal GC treatment on the development of the immune system have been evaluated in small series, which indicated that prenatal GC treatment may result in the alteration of inflammatory factors [6, 7], and thus contribute to the disturbance of immune system. However, reports about the mechanism linked prenatal GC exposure and autoimmunity are few.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that adipose type I IFN signaling protects against diet-induced metabolic dysfunction, though it mediates inflammatory responses. Another study reported that high-fat diet decreased IFN-γ production in rats [ 49 ]. As a target of IFNs family, viperin expression depends on the relative activity of IFN-β and IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Female rats received either a regular rat diet (Fwusow Taiwan Co., Ltd., Taichung, Taiwan; 52 g% carbohydrates, 23.5 g% protein, 4.5 g% fat, 10 g% ash, and 8 g% fiber) or an HFHS diet (D12331, Research Diets, Inc., New Brunswick, NJ, USA; 35.8 g% fat plus high sucrose [35.5 g% carbohydrate], and protein 23.0 g%) ad libitum for 8 weeks before mating and during gestation and lactation. Male SD rats were kept with female rats until mating was confirmed [36,40]. The size of the litter was normalized after delivery immediately to conform the amount of milk and maternal care equalized.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…Progeny body weight (BW) was determined every month since birth to four-month-old. At four-month-old, the rat progeny was sacrificed under anesthesia of Zoletil (Zoletil® 50; Virbac corporation, Carros, France) and xylazine (Rompun®, Bayer, Leverkusen, Germany), and blood samples were obtained by cardiac puncture as previously reported [39][40][41]. Retroperitoneal, mesenteric, epididymal, and subcutaneous fats were collected to measure adipose tissue weight [41].…”
Section: Experimental Processes For Sample Collectionsmentioning
confidence: 99%
See 1 more Smart Citation